Paul’s Missionary Strategies and their Replications in the Mission Outreaches of Lagos Metropolitan Areas of the Apostolic Church, Nigeria (2014)
Christianity, from inception, has been a missionary religion. The Acts of the Apostles and Pauline letters are replete with Paul‘s missionary activities and their contributions to contemporary churches. Many scholars have examined Paul‘s missionary journeys and strategies, but adequate attention has not been given to the connection between these strategies and those of the Lagos Metropolitan Areas of The Apostolic Church, Nigeria (LMATACN) which is a missionary organisation. This study, therefore, compared Paul‘s missionary strategies with those of LMATACN with a view to determining the Biblical basis and the effectiveness of the missionary enterprise of LMATACN. The study utilised Peter Wagner‘s Frontier Missionary Strategy, which underscores the relevance of Bible-centredness for mission work. In-depth interviews were conducted with purposively selected 50 clergy and 20 laity. Also, 220 copies of a questionnaire were administered to 32 pastors, 45 church officers and 143 members selected from LMATACN, comprising Lagos and Ogun States. Church records at the Mission Headquarters in Lagos were consulted. Data were subjected to exegetical analysis, with reference to selected passages in Acts and Pauline letters; and percentages. Paul adopted five missionary strategies: choice of principal cities and cultural centres for evangelism (Acts 28:30-31; Romans 15:24; 1Thessalonians 1:8), team-ministry (Acts 9: 28-30; Romans 12:3-4), use of house-churches (Acts 16:27-34; 1Corinthians 1:16), adoption of ―tent-making‖ (part-time) mission (Acts 18:3; 1Corinthians 9:6-15; 1Thessalonians 2:9), and contextualisation of the gospel message (Acts 9:19-22; 17:22-32). The Lagos Metropolitan Areas of The Apostolic Church, Nigeria also used five missionary strategies: rural evangelism, group rallies and conventions, house-churches, education and the use of print and electronic media for evangelism. Lucan accounts in Acts documented the success of the five missionary strategies of Paul, through which he established new churches in the Provinces of Galatia (Acts 14: 20), Macedonia (Acts 17:4), Achaia (Acts 18:8), and Asia (Acts 19:10) within ten years (AD 47-57). Contrariwise, only two of the five strategies of Paul were relatively adopted by LMATACN: team-ministry and the use of house-churches. Little or no attempt was made to use principal cities and cultural centres, ―tent-making‖ mission and contextualisation of gospel message. This resulted in the lack of financial self-sufficiency, non-autonomy of ministers and local churches, sour ministerial relationship, lack of indigenisation and poor contextualisation of the gospel. The deficiency was evident in the responses of the respondents, as 87.7% of the respondents agitated for non-stipendiary mission in LMATACN, like that of Paul; while 80.0% canvassed for autonomy of ministers and local churches. Majority of the respondents preferred contextualisation of the gospel message. The Lagos Metropolitan Areas of The Apostolic Church, Nigeria adopted only two out of the five missionary strategies used by Paul, which revealed an inconsistency with biblical standard, and made the mission less effective. Therefore, LMATACN and other mission-minded churches need to completely adopt all the strategies of Paul to enhance effective missionary work